EFFECTIVENESS OF ETHANOL EXTRACT MEAT FRUIT MAHKOTA DEWA (Phaleria macrocarpa (Scheff) Boerl) ON REDUCE URIC ACID LEVELS IN MALE MICE (Mus musculus) - Pikaulima, Pricilia; Rehena, Johanis Fritzgal; Arini, Ine (Universitas Pattimura, 2022)
Mahkota Dewa (Phaleria macrocarpa (Sceff.) Boerl.) is a medicinal plant that is used empirically as a medicine for various diseases, one of which is gout. This study aims to determine the ethanol extract of the crown of the gods in reducing uric acid levels in mice. This study used an experimental method with the research subject being male mice (mus musculus) and the object of research was the decrease in uric acid levels in mice when given treatment. The independent variable was the ethanol extract of the crown of the god flesh and the dependent variable was uric acid levels in male mice (Mus musculus). Data on the percentage decrease in uric acid levels was tested using one-way ANOVA (5% confidence level) followed by the Bonferroni test. The results showed that the dosage of ethanol extract of Mahkota Dewa fruit was 1.25; 2,5 and 5g/kgbw were able to reduce uric acid levels in the blood serum of male mice induced by potassium oxonate. of the five treatment groups, the average uric acid level with the negative control was 0.48 ± 0.04 mg/dl. Positive control was 0.62 ± 0.08 mg/dl. The ethanol extract dose of 1.25g/kgBB was 1.68 ± 0.13. The ethanol extract dose of 2.5g/kgbw was 1.62 ± 0.08 and the ethanol extract dose of 5g/kgBW was 1 ± 0.5.